Motivational push and pull factors influencing intentions to revisit Jordan as a MICE destination - Ramadan, Ammar; Kasim, Azilah (Turyzm/Tourism, 2024)
The main objective of this study is to examine the impact of push and pull factors on the intentions of international participants to revisit MICE events held in Amman, given that there are very few existing studies on the topic. This research is quantitative and employs a questionnaire method to collect data. For data analysis, partial least squares structural equation modelling (PLS-SEM) was utilized to test the research hypothesis with a purposive sample of 479 international visitors who had attended 14 MICE events held in Amman in 2022. The study revealed that networking opportunities, educational opportunities, destination image, travel cost, destination attraction and accessibility have a significant positive impact on revisit intentions. In terms of implications, these findings contribute to enriching push and pull theory in this context among MICE participants. In practical terms, the findings contribute to empowering planners, managers, marketers and organizers in the MICE industry in terms of creating and promoting effective strategies related to MICE tourism. The findings are anticipated to be useful for conference organizers, enabling them to attract repeat participants in this extremely competitive event industry.